Representações do Sebastianismo no Tambor de Mina - CAMPOS, Paula Mariana Guedes (UNIFAP – Universidade Federal do Amapá, 2022)
This work discusses the representations of the Sebastianism in the Mina’s Drum in Brazil. Thus, in order to better understand the origins of the Sebastianism in Portugal, the main theoretical bases used are the works “O Sebastianismo – História Sumária (1987), by José Van Den Besselaar, and Império dos sonhos: narrativas proféticas, sebastianismo e messianismo brigantino (2010), by Luís Filipe Silvério Lima. In addition, for the discussion regarding the Sebastianism in the enchantment, the concepts of enchantment are utilized, especially in the Mina’s Drum, proposed by Mundicarmo Ferretti (2008) and by Sergio Ferretti (2013). It is therefore expected, with this research, to enlarge the knowledge about the Sebastianism in Mina’s Drum by means of new visions, reflecting upon the correlation of several historical, literary and religious aspects towards the Portuguese-Brazilian literature. This work aims at contributing for the approximation of the literary studies to the religious studies. At last, this research seeks to point out the relations of the Sebastianism with the Mina’s Drum.